High Expression of P53 protein in Recurrent Pregnancy Loss Could Play a Role in the Pathology!! - Abdul-Mohaymen, Nidhal; Al-Obaidi, Asmaa’ B.; Rasheed, Thanaa (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Recent data provide evidence that p53 plays a critical role in mediating pregnancy by regulating steroid hormone activation Objective: localization of semi quantitation tof por protein at the materno-fetal interface, in patients with recurrent pregnancy loss. Methods: Immunohistochemistry analysis of p53 protein using paraffin embedded sections of curate samples obtained from 40 women, who where divided into three groups: 24 women with RPL, 10 women with abortion for the first time, and 6 women with induced abortion. Results: The mean value of the expression of p53 protein in the RPL group was (65.8±2.16), which is significantly higher than that of the second group (48.0±2.81), and the third group (50.0±4.66), (p=0.000). Conclusion: High expression of p53 protein in women with RPL may have a role in accelerating placental apoptosis leading to failure of pregnancy.